Bridging the Financing Gap: Comparative Effects of Fintech Lending and Bank Credit on MSME Financial Performance - Tantri Octora Dwi Syah Putri; Yusniar Lubis; Elly Romy (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2026)
This study explores the effects of fintech lending and bank credit on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Medan City, Indonesia. The fast digital revolution in the financial sector has positioned fintech lending as an alternate financing source alongside conventional bank credit, which has historically functioned as the major formal funding vehicle for MSMEs. Despite the rising distribution of both financing schemes, their contribution to sustainable and equitably distributed financial performance among MSMEs remains ambiguous, highlighting the necessity for empirical inquiry. This study employs a quantitative explanatory method employing purposive sampling, targeting MSME owners who have received bank credit and/or fintech lending services. The sample size was determined using the Lemeshow formula for an unknown population, resulting in 100 respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software, combining measurement model evaluation, structural model assessment, and hypothesis testing through bootstrapping processes. This study contributes to the financial inclusion and MSME financing literature by providing comparative empirical evidence on the effectiveness of digital and conventional finance in increasing MSME financial performance. The findings are likely to offer practical insights for MSME actors, financial institutions, and policymakers in designing more flexible, inclusive, and sustainable financing strategies.